Measuring the body composition of antarctic fur seals (Arctocephalus gazella): Validation of hydrogen isotope dilution - John Arnould; LL Boyd; JR Speakman (1996)
We examined the accuracy of hydrogen isotope dilution (tritium and deuterium) as a means of determining total body water (TBW), and hence body composition, by comparison with whole-carcass chemical analysis in five adult female and four pup Antarctic fur seals. On average, tritium isotope (HTO) dilution overestimated TBW by 1.92% ± 1.00% (n = 9). Deuterium isotope (D 2 O) dilution also overestimated TBW (1.71% ± 1.74%, n = 5), but this trend was not significant. The following equations were developed for predicting TBW from by-drogen isotope dilution estimates: TBW (kg) = 0.11 + 0.97 · HTO space (kg) (r 2 = 0.999, n = 9, P < 0.0001) and TBW (kg) = 2.10 + 0.89 · D 2 O space (kg) (r 2 = 0.980, n = 5, P < 0.001). Whole-carcass chemical analysis showed adult females were composed of 14.5% ± 1.0% total body lipid (TBL), whereas pups were composed of only 9.4% ± 1.0% lipid. Adult females bad lower TBW contents (60.1% ± 0.7%) than pups (67.6% ± 1.2%) and, consequently, higher energy contents (adults, 10.59 ± 0.30 MJ · kg -1 pups, 8.24 ± 0.41 MJ · kg -1 ). Pups bad higher ratios of TBW to lean body mass (LBM) (0.747 ± 0.009) than adults (0.707 ± 0.004), which indicates they had not yet reached chemical maturity. The following best-fit predictive equations based on TBW and body mass (BM) were developed for TBL, total body protein (TBP), total body ash (TBA), and total body gross energy (TBGE): TBL (kg) = 0.875 · BM (kg) - 1.187 · TBW (kg) - 0.633 (adults); TBL (%) = 66.562 - 0.845 · TBW (%) (pups); TBP (kg) = 0.058 · BM (kg) + 0.209 · TBW (kg) + 0.996 (adults); TBP (kg) = 0.267 · BM (kg) - 0.130 · TBW (kg) + 0.087 (pups); TBA (kg)= 0.071 · TBW (kg)- 0.088 (adults and pups); TBGE (MJ · kg -1 ) = 34.1 - 0.391 · TBW (%) (adults); TBGE (MJ · kg -1 ) = 31.7 - 0.347 · TBW (%) (pups). With the use of these predictive equations, hydrogen isotope dilution is an accurate means of determining body composition in live Antarctic fur seals. Differences in these relationships between adults and pups, and in comparison to those ...